GDF10 inhibits cell proliferation and epithelial–mesenchymal transition in nasopharyngeal carcinoma by the transforming growth factor-β/Smad and NF-κB pathways. (18th December 2021) - He, Feng; Feng, Guofei; Ma, Ning; Midorikawa, Kaoru; Oikawa, Shinji; Kobayashi, Hatasu; Zhang, Zhe; Huang, Guangwu; Takeuchi, Kazuhiko; Murata, Mariko
Abstract: Growth differentiation factor-10 (GDF10) belongs to a member of the transforming growth factor-β (TGF-β) superfamily. Dysfunction of the TGF-β pathway can lead to carcinoma progression. Previous studies have shown that GDF10 acts as a tumor suppressor gene in some cancers. However, the molecular mechanisms of the association between GDF10 and cell functions in nasopharyngeal carcinoma (NPC) remain unclear. In this study, the expression and methylation levels of GDF10 were studied in human subjects and cell lines. Furthermore, overexpression of GDF10 was used to explore its biological function and potential mechanism in NPC cell lines. GDF10 was downregulated in NPC owing to its aberrant promoter methylation. After treatment with 5-aza-2′-deoxycytidine, the expression of GDF10 in NPC cells was reversed. We also confirmed that the overexpression of GDF10 significantly inhibited cell proliferation and tumor growth both in vitro and in vivo, respectively. Additionally, GDF10 overexpression in NPC cells attenuated migration and invasion and inhibited epithelial-to-mesenchymal transition with a decrease in nuclear Smad2 and NF-κB protein accumulation. GDF10 was silenced owing to its promoter hypermethylation, and it might originally act as a functional tumor suppressor via TGF-β/Smad and NF-κB signaling pathways in NPC. Graphical Abstract: